2009
DOI: 10.1111/j.1365-2133.2009.09395.x
|View full text |Cite
|
Sign up to set email alerts
|

Report from the 67th Annual Meeting of the American Academy of Dermatology

Abstract: The 67th Annual Meeting of the American Academy of Dermatology took place in San Francisco on 6-10 March 2009. The flavour of this busy but well-organized convention was a mixture of practical, hands-on teaching sessions, led and delivered by experts, with breakthrough cutting-edge scientific sessions. Aesthetic dermatology comprised a significant part of the meeting. It is impossible to encompass all the important presentations made at the meeting and satellite symposiums, but we highlight here a few medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 253 publications
(256 reference statements)
0
6
0
Order By: Relevance
“…Despite a possible selection bias due to a small number of patients in this cohort, it has been suggested that physicians should remain vigilant and perform regular skin examination in patients with psoriasis on anti‐TNF treatment. These facts should remind us yet again that new classes of drugs should be treated with caution until a sufficiently high number of patients have been treated and long‐term follow‐up data are available 64 …”
Section: Inflammatory Dermatoses and Infectionsmentioning
confidence: 99%
“…Despite a possible selection bias due to a small number of patients in this cohort, it has been suggested that physicians should remain vigilant and perform regular skin examination in patients with psoriasis on anti‐TNF treatment. These facts should remind us yet again that new classes of drugs should be treated with caution until a sufficiently high number of patients have been treated and long‐term follow‐up data are available 64 …”
Section: Inflammatory Dermatoses and Infectionsmentioning
confidence: 99%
“…Malignant melanoma kills a disproportionately large number of young people, and it is not surprising that significant and sustained efforts have been directed towards the improvement of its prevention, diagnosis and treatment 44–98 . There has been increasing interest in dermoscopy, as several studies have suggested improved diagnostic accuracy compared with clinical diagnosis by naked eye examination 47 .…”
Section: Dermatological Surgery and Oncologymentioning
confidence: 99%
“…Similarly to SLE, ankylosing spondylitis and rheumatoid arthritis, psoriasis is now recognized as a truly multisystem inflammatory disease and thus as a major risk factor for atherosclerosis 44,177,178,205–207 . Although psoriasis is associated with classical cardiovascular risks including smoking, hypertension, hyperlipidaemia, diabetes and metabolic syndrome, psoriasis itself has now been proved to be a major independent risk factor for myocardial infarctions, strokes, peripheral vascular disease, cardiovascular and overall mortality 177,178,208–210 .…”
Section: Inflammatory Dermatosesmentioning
confidence: 99%
“…Although psoriasis is confined to the skin, it is associated with psoriatic arthropathy in about 10% of patients, and more rarely with other autoimmune conditions such as Crohn disease. However, the evidence is now accumulating that, similarly to other chronic inflammatory diseases such as systemic lupus erythematosus and rheumatoid arthritis, psoriasis may in fact be a true systemic inflammatory process, intimately linked with atherosclerosis 4,5 …”
mentioning
confidence: 99%
“…However, the evidence is now accumulating that, similarly to other chronic inflammatory diseases such as systemic lupus erythematosus and rheumatoid arthritis, psoriasis may in fact be a true systemic inflammatory process, intimately linked with atherosclerosis. 4,5 Thirty-seven years ago, McDonald and Calabresi 6 made an appeal to the attention of the medical community about a possible link between psoriasis and cardiovascular disease. However, it took another 33 years and a large UK GP database before Gelfand et al 7 established an unequivocal and clinically highly significant link between psoriasis and atherosclerosis.…”
mentioning
confidence: 99%